2013
DOI: 10.1007/s11195-013-9298-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Sexuality as Standard Care in People with an Upper Limb Deficiency: Taboo or Necessary Topic?

Abstract: The purpose of this paper is to analyze whether professionals who work with people with an upper limb deficiency (ULD) received questions about sexuality from their patients and whether they addressed sexuality themselves, and to analyze their knowledge and comfort level, approach and attitudes towards sexuality. An online questionnaire, including questions on self-perceived sexological competence and the Knowledge, Comfort, Approach and Attitudes towards Sexuality Scale (KCAASS) was used to asses these aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, most participants indicated that sexuality was not discussed with them at all during the rehabilitation process, let alone with the partners. This was also in line with what was found in other studies [12,[36][37][38]. Nonetheless, most participants would have liked more information about sexuality and amputation.…”
Section: Discussionsupporting
confidence: 90%
“…However, most participants indicated that sexuality was not discussed with them at all during the rehabilitation process, let alone with the partners. This was also in line with what was found in other studies [12,[36][37][38]. Nonetheless, most participants would have liked more information about sexuality and amputation.…”
Section: Discussionsupporting
confidence: 90%
“…Sex is a topic that is both taboo and critical to one's self-identity. [1][2][3][4][5][6][7][8] Discussing sexual issues in a health care setting may seem like a profound idea, yet is a common desire vocalized by an abundance of patient populations seeking to improve all aspects of their health. [9][10][11] While a variety of factors contribute to the presence of sexual dysfunction, chronic disease is a frequent component.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,14,16 Many studies emphasize the importance of discussing patients' sexual health concerns, with benefits ranging from improved mental and physical health, improved quality of life, and relationship success. [1][2][3][4][5][6][7][8] Physical therapists are one of many health care providers who must be capable of actively engaging with every system of the body in clinical practice. Thus, sexual dysfunction may be a common complaint among the patients with whom physical therapists will interact.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations